A Study of Greek Building Materials as Indoor Radon Sources - Savidou, A.; Raptis, C.; Kritidis, P. (HNPS Advances in Nuclear Physics, 2020)
A survey of radon emanation in building materials commonly used in Attica has initiated at our laboratory as part of a broader EU program. The objective is to obtain a characterisation of the Greek building materials as indoor radon sources and identify the cases where some specific countermeasures should be applied. Up to now, bricks commonly used in Attica have been studied for both radium content and radon emanation. Gamma-ray spectroscopy techniques, as well as radon exhalation measurements, have been employed. For determination of radon exhalation rate, besides the trivial method which consist of a single measurement of radon concentration in a closed vessel containing the sample, a short-time continuous accumulation/counting method has been established. The results of exhalation measurements have been used together with high-resolution gamma-spectrometry in order to determine radon emanation coefficients.